Influência dos ciclos térmicos na microestrutura e propriedades mecânicas de um aço maraging 300 18% Ni - Loureiro, Rodrigo de Carvalho Paes (2020)
Maraging steels are martensitic steels with a very low carbon content. They are intended for use in areas where great mechanical stresses and good fracture toughness are required. The objective of this work is to verify the influence of different heat treatment cycles on the microstructure and mechanical properties of a maraging 300 steel. In this work, the samples were cut, laminated and subjected to thermal cycles. The effects of these thermal cycles on the mechanical properties were evaluated by measuring the hardness, toughness, strength limit. The grain size of the prioraustenite was characterized by optical microscopy, backscattered electron diffraction (EBSD) and X-ray diffraction, electron microscopy for analysis of the microstructure and fracture surfaces. The thermal cycles at 650 and 700 °C, repeated 10 times, followed by solubilization at 820 °C and aged at 480°C promoted the formation of heterogeneous size of prioraustenite grains, while at 930 and 1050 °C, repeated 5 times,followed by aging at 480 °C provided additional growth of the recrystallized grains after the first cyclethermal. The results of the mechanical properties showed for the sample 700 °Crepeated 10 times, followed by solubilization at 820 °C and aged at 480 °Chigher values of toughness and hardness. The tensile properties at room temperature were not strongly affected by the grain size of the prioraustenite, however, there were gains in the ultimate tensile properties when the material is subjected to thermal cycles at 650 and 700 °C, repeated 10 times, followed by solubilization at 820 °C and aged at 480 °C.